Spontaneous retroperitoneal haemorrhage in a young adult. (22nd March 2014) - Baksi, Aditya; Gupta, Shahana; Ray, Udipta; Ghosh, Shibajyoti
Abstract : We report a rare case of a primary adrenal cortical malignancy presenting with spontaneous retroperitoneal haemorrhage in a young adult. To the best of our knowledge, this is the thirteenth such case to be reported in the English literature.